Isolamento, identificação química e bioprospecção de metabólitos secundários nas folhas de annona crassiflora Mart. - Gisele Avelar Lage (2011)
This dissertation presents the phytochemical study and the biological evaluation of the leaf ethanolic extract of Annona crassiflora Mart. Annona crassiflora is a native tree of the Cerrado area, popularly known as araticum, belonging to the Annonaceae family. The phytochemical study of the hydroalcoholic portion of the leaf ethanolic extract led to the isolation and identification of two O-glycosides: quercetin-3-O-ß-D-glycopyranosil(1.6)-O-a-L-arabinoside, known as peltatoside, and quercetin-3-O-a-L-arabinopiranoside; an aporphine alkaloid: norstephalagine; and a flavan-3-ol: (-)-epicatechin. Structures of the known compounds were established by 1H NMR (400 MHz), 13C NMR (100 MHz), DEPT, HSQC, HMBC, COSY, ESI-MS, UV/VIS spectroscopy and literature data comparison. Although flavonoids have been described in Annona genus this is the first time that they have been isolated and unambiguously identified in Annona crassiflora, in Annona genus and in Annonaceae family. In spite of the aporphine alkaloid norstephalagine being isolated in Xylopia genus, never have been described in A. crassiflora and in Annona genus. The (-)-epicatechin was also isolated and characterized for the first time in A. crassiflora.The leaves ethanolic extract, some of its fractions and its isolated compounds were evaluated front of antioxidant activities, larvicidal and antimicrobial. The leaf ethanolic extract, one of its fractions and their precipitate showed antimicrobial activity against Stafilococcus aureus, Bacillus cereus, Salmonella typhimurium and Escherichia coli, as well as Candida albicans. The flavonoids, the alkaloid and the flavan-3-ol isolated showed antioxidant activity in the TLC ß-carotene bleaching and DPPH TLC assay. In the Brine Shrimp test only the alkaloid norsthephalagine presented good activity (EC50= 2.91 µg/mL)